Effect of Non-Genetic Factors on Milk Yield, Milk Constituents and Feed Efficiency in Lactating Kankrej Cows - Dr. Y. M. Gami; Dr. Rakeshbhai R. Chaudhary; Dr. H. H. Panchasara; R. P. Deriya (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
A study was carried out to assess the effect of season and parity on milk yield, milk composition, feed efficiency and return over feed cost in lactating Kankrej cows. Forty-nine cows of first to fourth parity were randomly selected at three weeks postpartum with an average body weight of 441.10 kg. Milk yield was recorded daily during the monsoon, winter and summer seasons, while feed intake and milk composition were measured at weekly intervals. Season had no significant effect on milk yield; however, dry matter intake was higher in winter than in monsoon and summer. Feed efficiency was superior in the summer, followed by winter and monsoon. Milk fat, solids-not-fat, protein and lactose percentages were higher in summer. The higher return over feed cost observed during summer may be attributed to the well-known adaptability of Kankrej cattle to semi-arid, hot and dry environments, which helps maintain productivity and economic efficiency under elevated temperatures. Milk yield increased with parity, being highest in the third and fourth parities and lowest in the first. Parity did not affect dry matter intake, but feed efficiency increased linearly from first to fourth parity. Milk fat percentage was lowest in the first and highest in the fourth parity. Return over feed cost increased with advancing parity, with higher values in third and fourth parities, reflecting improved productive and economic efficiency in later lactations. It was concluded that season significantly affected feed intake, feed efficiency, milk composition and return over feed cost, whereas parity also significantly affected milk yield, milk fat, feed efficiency and return over feed cost in Kankrej cows.
Keywords: Feed efficiency; Kankrej cow; Milk composition; Milk yield; Parity; Season